Research on Bionic Image Design of Excavator Based on Eye Movement Experiment - Yunsheng XIN; Xinyu LI; Wei BAI; Zhucheng DUAN; Haolin LI; Nina SU (Taiyuan Ligong Daxue xuebao, 2023)
In order to meet the modeling design needs of construction machinery products represented by excavators, by combining image bionics, semantic difference method, and eye tracking experiment, a modeling design process system with reference value was proposed. Excavator was taken as the research object and the image bionic object was reasonably selected. The biological characteristics and styling characteristics of excavator were analyzed, so as to establish the mapping relationship between biological bionic characteristics and excavator modeling characteristics. With the help of multiple permutations and combinations, different design schemes were formed, and eye tracking experiments were used to collect data to evaluate the modeling. The design process proposed in this paper provides a new idea for the modeling design of construction machinery to a certain extent.